Ahoy, red rock!—american mining investors in Cedros Island, Baja California - Núñez Tapia, Francisco Alberto (My University, 2021)
The islands of Baja California had a compelling role in the developingeconomy of the Southwest of the United States predominantly in thelast decade of the nineteenth century and at the turn of the twentiethcentury, because the Mexican government could not surveil its ownmaritime space in the northwest part of the country and this resulted inAmerican ventures that exploited its natural resources that wentunsanctioned the vast majority of the time. In regarding the ore deposits,Cedros Island was heavily sought out by different American companiesdue to its large mineral veins that needed to be exploited legally, as aresult of large investments they had to spend to make it work.In this article, I present my ongoing research regarding the Americancompanies that operated in Cedros Island between 1889 and 1914; thequestion posed is what led them to invest in a desolate island of BajaCalifornia and if there were significant implications in this binationalregion regarding the mining activities carried out on the island. Theimportance of this study is to understand why the resources that wereexploited and trafficked were of interest mostly to the Southern Californiaeconomy, and its connections to the mining sectors of the Southwest ofthe United States.Likewise, the importance of this story is to shed light on miningactivities carried out in Baja California that, although local scholars haveapproached it in the mainland mining districts of the region, they havefailed to study it on the islands adjacent to the peninsula; the ore depositsfound in Cedros Island comprise one of those cases. (20) (PDF) Ahoy, Red Rock! —American Mining Investors in Cedros Island, Baja California. Available from: https://www.researchgate.net/publication/351807245_Ahoy_Red_Rock_-American_Mining_Investors_in_Cedros_Island_Baja_California#fullTextFileContent [accessed Feb 26 2024].
Journalt of la Southwest
Keywords: American mining; Investors; Campus Mexicali